Sharing Screen Capture Android Application - Uttaram, I G.; Mahendra Darmawiguna, I Gede; Gede Sunarya, I Made (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2013)
Currently education and technology are something that is very closely related. Education would become more interesting through technology. Class activities in the learning process become more interactive by using projector in presentation. Therefore, the teacher easily teaches the knowledges to the students because they use more imaginative audio and visual media. At this time, mobile devices has become a primary needs. The children, teenagers, and adults use it very well, such as notebooks, smartphones, and tablet pc. Especially with the spread of the android os as public resources, thus making the penetration of mobile devices such as smartphones and tablet pc are becoming increasingly vociferous. Even the mobile world has created a new mobile device that term "phablet" (phone tablet). Therefore, it is possible to use these tools to better facilitate the learning process and making it easier for application development, particularly for educational applications . This research aims to (1) design a Capture Screen Sharing application, (2) implement Capture Screen Sharing application design. The research methods used in this research is the development. Sharing Screen Capture is an application that will be developed by the researcher using android os to simplify the presentation process. This application is expected alternative to replace the projector with mobile devices and simplify the learning process for using mobile devices owned by students in showing the presentations from teachers's android devices which connected to the same wireless network.